Effects of Skin Mast Cells on Bleeding Time and Coagulation Activation at the Site of Platelet Plug Formation - Kauhanen, Petteri; Kovanen, Petri T.; Reunala, Timo; Lassila, Riitta (Thrombosis and Haemostasis, 1998)
We studied the effects of stimulated skin mast cells on bleeding time and thrombin generation which was measured using prothrombin fragment F 1+2 (F 1+2) and thrombin-antithrombin-III-complex (TAT). In 10 patients with urticaria pigmentosa (chronic cutaneous mast cell accumulation) the mean bleeding time was significantly prolonged in wounds made on urticaria pigmentosa lesions vs. normal skin (460 ± 34 vs. 342 ± 27 s, p = 0.005). In 10 atopic subjects skin incisions were made on prick-tested sites 30, 60, 120 and 240 min after administration of an allergen (acute mast cell stimulation), histamine or vehicle. The mean bleeding time was significantly prolonged at all time points, being maximal at 120 min (60% prolonged) in wounds made on allergen-stimulated skin areas (p <0.01) compared with histamine or vehicle sites. Administration of allergen or histamine lowered the TAT concentration in the bleeding-time blood. Furthermore, TAT and F 1+2 levels in the bleeding-time blood were lower at 60, 120 and 240 min after allergen or histamine application in comparison with samples collected at 30 min. We conclude that skin mast cells can regulate primary hemostasis by prolonging bleeding time and by inhibiting thrombin generation.